Caracterização da comunidade bacteriana de Baccharis dracunculifolia, com e sem galha causada por Baccharopelma dracuncufoliae - Raiana Silva Menezes de Santana (2013)
Bacteria are ubiquitous, inhabiting different environments, including other living beings. Composition and diversity may be affected by the health or disease conditions of the host organism. In this scenario, this work characterized the endophytic bacterial communities of Baccharis dracucunlifolia endorhizosphere affected by the gall insect Baccharopelma dracuncufoliae and leaves of male plants, with and without B. dracuncufoliae gall, from the partial sequencing of 16S rRNA gene using different high throughput platforms: Ion Torrent and Illumina HiSeq 2000. Furthermore, we compared the composition of these communities, using restriction analysis of the amplified rDNA (ARDRA). Phylogenetic analysis of the microbiota of endorrizosfera showed a diverse and complex community, represented by 17 phyla. It is noteworthy that 50 % of the sequences of 16S rDNA were not classified in the phylum level. Proteobacteria predominated (28.7 %), followed by the phyla Actinobacteria (11.5%) and Acidobacteria (2.6%). The compositions of the bacterial communities from the leaves of healthy and affected plants were significantly different (p < 0.05). In both libraries, Proteobacteria was the most abundant phylum. Other phyla found were Actinobacteria, Firmicutes, Bacteroidetes and Chorobi. The endophytic microbiota of B. dracuncufolia harbour metabolically diverse bacteria with potential to degrade wide variety of compounds, which is expected when studying such a rich plant secondary metabolites as B. dracunculifolia. Unlike Illumina HiSeq 2000 sequencing, the ARDRA profile revealed no differences between male healthy and gall plants, and female healthy and gall plants. The results of this study indicate that B. dracunculifolia houses a diverse and complex community, and that the presence of galling insect interferes in their bacterial composition.